Sistem Pusat Pelayanan Anak Untuk Optimalisasi Perkembangan Anak Berbasis Web - Ferianti, Lydya Ayu; Nugraha, Fajar (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
In the current era, advances in information technology have led to an urgent need for more efficient management systems and services, especially in the context of children's services. Certified Independent Study offers students the opportunity to prepare themselves in full stack web development, with the aim of producing high quality and competitive web applications. The developed children's center web application is designed to handle various aspects of children's administration and services as a whole. The main features of the application include registration, health monitoring, education management, as well as coordination of social activities. This integrated platform not only allows parents and related parties to access real-time information but also facilitates better collaboration in providing optimal services to children. The research shows that the method applied in the development of this application is effective in improving efficiency and ease of use, with the results of the System Usability Scale (SUS) assessment reaching an average of 83.3 which indicates the predicate